Elis schoolbase / Zuraidah Sipon ... [et al.] - Sipon, Zuraidah; Mohamed Yousop, Nur Liyana; Mohd Hassan Abdullah, Norhasniza; Roslan, Shashazrina; Ahmad, Zuraidah; Ramdhan, Nur'Asyiqin (2022)
School choice is an important decision that every parent needs to make even for their normal children and what more with the children with disabilities. In Malaysia, while school choice options are available to all families regardless of their socio-economic status, parents with special needs children are facing issues of limited school choices to enroll their kids for a reliable special education critically at the early intervention stage. In general, there are various issues that need to be considered in choosing schools such as teacher quality, school reputation, class size, distance and safety, parental and public opinion and value attached to education, sociological and cultural factors and even market forces. With all the issues that parents need to consider, coming up with a decision on which school is the best for their special kids can be a never-ending process. ELIS SchoolBase provides a handy and easily accessed tool for a quick school choice decision. It proposed guidelines on how to make school choice decisions and give an idea to parents about the dimensions (based on ELIS framework) that they should investigate when considering the school placement for their school-age children. Parents can conduct a self-check based on the dimensions developed in the system and it is a reliable tool because questionnaires are developed based on research. ELIS SchoolBase can be used anywhere and anytime without hassles.